1999
DOI: 10.1007/s004840050123
|View full text |Cite
|
Sign up to set email alerts
|

Human morphology and temperature regulation

Abstract: For nearly a century individuals have believed that there is a link between human morphology and one's thermoregulatory response in adverse environments. Most early research was focussed on the rate of core cooling in a male adult population and the role of subcutaneous adipose tissue, surface area and the surface-area-to-mass ratio in one's ability to withstand varying degrees of cold stress. More recently research has addressed heat tolerance in various populations, exploring the role of subcutaneous adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 39 publications
2
75
1
1
Order By: Relevance
“…One possibility is that overweight individuals might have compromised thermoregulatory ability, resulting in higher core or brain temperatures. [54][55][56][57] These are known to be associated with reduced ratings of pleasure and comfort during exercise. 58 Another possibility, supported by anecdotal reports collected during the present study, is that, as the intensity increases, overweight adults tend to experience more skeletal and muscular aches and pains than normalweight adults.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that overweight individuals might have compromised thermoregulatory ability, resulting in higher core or brain temperatures. [54][55][56][57] These are known to be associated with reduced ratings of pleasure and comfort during exercise. 58 Another possibility, supported by anecdotal reports collected during the present study, is that, as the intensity increases, overweight adults tend to experience more skeletal and muscular aches and pains than normalweight adults.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this may be that smaller total body and muscle mass and larger body surface to massratio expose to stronger body cooling 41) thus increasing the experience of musculoskeletal symptoms 35) . There are several epidemiological studies in thermoneutral conditions [42][43][44] about the effect of e.g.…”
Section: Musculoskeletal Symptomsmentioning
confidence: 99%
“…It theorizes that adipose tissue has a strong insulating capacity, which inhibits heat dissipation, resulting in a higher tendency for VMS events in order to release the heat. 61,62 In contrast, the thin hypothesis states that women with greater body fat or higher mean body weight will have a reduced risk of VMS because of potentially higher estrogen concentrations (androstenedione is aromatized into estrone in adipose tissue). 63,64 The latter model is questioned by the findings of a case-control study by Gallicchio et al 65 and a cross-sectional study by Schilling et al, 66 who found significantly lower levels of estrogen in obese women (BMI 35 kg=m 2 , BMI >30 kg=m 2 , respectively) compared with normal-weight midlife women (BMI <25 kg=m 2 ).…”
Section: Body Mass Index and Obesitymentioning
confidence: 99%